Analisis Perhitungan Rem Tromol Roda Belakang Mobil Suzuki Mega Carry - Defa Muchlis Fauzi; Viktor Naubnome; Nadjmudin Fauji (Jurnal Ilmiah Wahana Pendidikan, 2022)
The drum brake is one of the brake systems on the back of the Suzuki Mega Carry. Drum brakes work due to friction between the drum and the brake pads. the calculation in this study aims to aspects of safety, strength and feasibility of brakes. The material used in this drum brake is asbestos printed on steel or cast iron with a coefficient of friction of 0.3 and the maximum pressure is 350-1000 Kpa. The calculation that has been planned is that the normal force on the rear wheels is 347.1 N. The acceleration price is 8.23 ​​m/???? 2 . The permissible frictional force on the asphalt is 104.13 N. The force generated from the brake pedal is 82.5 kgf. The upper drum brake spring is the maximum force of the spring with a diameter of 2 mm of spring wire and a spring diameter of 30 mm with a spring length of 106 mm is 82.45 N. The maximum spring force with a spring wire diameter of 1 mm and a spring diameter of 10 mm with a spring length of 106 mm is 80.8 N.